Accelerated Monte Carlo perturbation calculation by surface recovery. (1st June 2023) - Berry, L.; Truchet, G.; Bonaccorsi, T.
Highlights: New Monte Carlo methodology for sensitivity studies to geometrical perturbations. Development of the surface recovery principle to improve simulations efficiency. Study of the effect of the perturbation of in-core guide tubes position. Effect of fuel assembly position perturbation in a nuclear reactor. Abstract: This paper address the problem of calculating the sensitivity of power distribution measurements to detector and fuel assemblies small displacements using a Monte Carlo code. A two-scale approach using the principle of surface recovery is proposed. The first step is performed on the whole geometry where all of the characteristics of the particles crossing surface defined by the user are stored in source files. In a second step, previously recorded particles are reinjected independently to estimate each detector response on simplified geometry. Reusing the previously stored particles on smaller geometries, significantly accelerates the simulation and reliable estimations of the displacement influence can be made. These methodologies are not limited to detector and fuel assemblies movements. They can also be used when performing a parametric study concerning the geometry or the constituents of the core under study.